THE EFFECT OF COMPANY PROFITABILITY AND SUSTAINABILITY REPORT DISCLOSURE ON INVESTOR REACTION (State-Owned Companies Listed On Indonesia Stock Exchange for The Period 2017-2021) - Rosa Fitriana; Syafdinal Syafdinal; Rini Susiani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Researchers are interested in examining the topic of how investors react to corporate sustainability disclosure information and company profitability which then becomes a direct driving factor related to investor reactions as the topic under study. The extent of corporate sustainability report disclosure is an increasingly common discourse in the business world in Indonesia, where this phenomenon is triggered by the increasingly globalized trend regarding corporate sustainability practices in business. Research on investor reactions as influenced by corporate profitability and the extent of sustainability report disclosure has produced different findings. The sample in this study is state-owned companies in Indonesia listed on the Indonesia Stock Exchange in 2017-2022 whose annual reports contain corporate sustainability activities and can be accessed through the IDX website, using purposive sampling technique. The analysis technique used in this study is descriptive analysis to provide an overview of the research variables and multiple regression analysis to determine the effect of profitability and corporate sustainability disclosures on investor reactions.